Pregnancy with Gilbert syndrome - Susmitha, Bhupanapati; Niroopama, Pushpagiri; Manasa, Kopperla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
A rare case of Gilbert syndrome during pregnancy was reported at Narayana Medical College and Hospital's obstetrics department. Due to the fact that it was an extremely rare case with a typical presentation, it was properly studied and analysed to provide a thorough case report. A 36-week-pregnant primigravida who had been having nausea, vomiting, stomach pain, myalgia, and a yellowish discoloration of both the skin and sclera for the past five days presented to Narayana Medical College and Hospital. She consistently suffered having similar symptoms at 14 and 24 weeks. She had icterus, signs of dehydration, a uterus that corresponds to period of gestation, and a good fetal heart rate. Examination revealed that all of the obtained investigations were normal, with the exception of mild unconjugated hyperbilirubinemia and hypoglycemia. After the dehydration and jaundice were treated, the patient's symptoms improved, and she was discharged from the hospital after a week. Later she underwent an emergency caesarean section due to fetal distress after being admitted during pregnancy at term, and she gave birth to a 3 kg female baby. Mother and baby both were fine postoperatively. Due to its rarity, this case was documented. Almost all of the patients had decreased uridine diphosphate glucuronosyl transferase activity (UDPGT).